2014
DOI: 10.1016/j.jlumin.2013.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of high optical quality CdSe thin films deposited by close-spaced vacuum sublimation

Abstract: a b s t r a c tPolycrystalline CdSe thin films (d¼ 0.1-3.0 μm) have been deposited on a glass substrate by means of the close-spaced vacuum sublimation technique. X-ray diffraction measurements have shown that the films obtained at Т s 4473 K have only wurtzite phase. The influence of deposition conditions, in particular, the substrate temperature on the photoluminescence (PL) of CdSe films spectra was investigated. This let us study the effect of glass substrate on their optical quality as well as determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…These energy values coincide with the corresponding energy for bulk CdTe crystal. The presence of intense exciton line indicates a fairly good optical quality of the investigated semiconductor films [19]. It should be noted that the shape of A°X-line is practically symmetric.…”
Section: Photoluminescence Of CD 1 à X Zn X Te Filmsmentioning
confidence: 68%
See 2 more Smart Citations
“…These energy values coincide with the corresponding energy for bulk CdTe crystal. The presence of intense exciton line indicates a fairly good optical quality of the investigated semiconductor films [19]. It should be noted that the shape of A°X-line is practically symmetric.…”
Section: Photoluminescence Of CD 1 à X Zn X Te Filmsmentioning
confidence: 68%
“…On the other hand, this energy may be caused by DAP transitions with the participation of shallow donor centers, which have ionization energy of 20 meV, and also can be caused by Al residual impurity atoms situated at Cd sites [53]. However, in that case we would have observed relative increasing of (e,A)-transition intensity with temperature raising [19] in the PL spectrum. Other very broad PL band at 1.497 eV corresponds to so-called D PL band, caused by the presence of point and extended defects of dislocation type as well as microstrains in the films [50,54].…”
Section: Photoluminescence Of CD 1 à X Zn X Te Filmsmentioning
confidence: 71%
See 1 more Smart Citation
“…Since the binding energy of BE (A 0 X-line) is equal ~5 meV [43], the band gap of CdTe sample is equal to 1.606 eV that coincides with the corresponding value for bulk CdTe. The presence of intense excitonic line indicates a fairly good optical quality of the investigated semiconductor films [62]. The PL band at 1.547 eV is caused by the recombination of free electrons and acceptor centers ((e,A)-transition) [1,14].…”
Section: Photoluminescence Studiesmentioning
confidence: 99%
“…Curves 1-4 correspond to the films obtained at T s equal to 893 K, 773 K, 473 K and 373 K, respectively. The analysis of the spectrum for the CdSe films obtained at T ¼893 K, performed by us in the work [40] showed that the high intensity line observed at 1.7357 eV and other lines at 1.7095 eV, 1.6833 eV and 1.6571 eV are associated with zero-phonon I DAP1 -line and its 1LO-, 2LO-and 3LO-phonon replicas. This emission is caused by recombination of the donor-acceptor pairs (DAP1s) with participation of Na or Li residual acceptor impurities in CdSe films [41][42][43][44].…”
Section: Photoluminescence Of Cdse Filmsmentioning
confidence: 91%